ATH-THIBBUN NABAWÎ : KAJIAN METODOLOGI PEMAHAMAN HADIS - Nur, Budiman Muhammad (DIRAYAH : Jurnal Ilmu Hadis, 2022)
Ath-thibbun Nabawî, are the words and actions of Prophet related to overcome disease epidemic, diseases cure, and patient care. This method has been practiced by the Prophet Muhammad Saw. during his life, and the theologians recommend that we must do this method when we are indisposed. However, in reality, people often misunderstand it, among the causes of the error is the mixing of goals and objectives to be achieved by temporary means. Actually, what are local means are regarded as a goal. So that, we found those who recited the Prophet's medicine, claimed that modern medicine is not considered the sunnah, as a Muslim should be able to be cooperative in accepting the development of science, without the slightest reducing belief in Prophet’s medicine method, based on the science development has been faund the various forms of better and more effective treatment. Because of that we should be choose the better and effective one without denying the positive values ​​and wisdom contained in the Prophet Saw. tradition related to treatment using certain materials. It's just because the healing material in the Prophet's tradition is a tools, the emergence of the hadith cannot be separated from its historical, sociological, and anthropological influences. Even sometimes these problems come from the Prophet's idea and experiences as a human being (af'al jibiliyyah).